MENDORONG PERUBAHAN: PERAN NILAI HARGA, KESESUAIAN HAMBATAN INFRASTRUKTUR, PENGARUH SOSIAL, DAN INSENTIF PEMERINTAH DALAM MEMBENTUK MINAT GENERASI Y UNTUK MENGADOPSI KENDARAAN LISTRIK DI JABODETABEK - Syah Fahlevi, Mochammad Reza; Siregar, Reza Poetra; Mustikasari, Faranita (JURNAL LENTERA BISNIS, 2025)
Air pollution in Jakarta continues to increase annually, along with the growing number of vehicles on the road. This situation has pushed the electric vehicle sector to develop and adapt rapidly in an effort to mitigate environmental problems in Jakarta. Jakarta is a potential market for both two-wheeled and four-wheeled electric vehicles. However, although Jakarta is one of the largest markets for electric vehicle adoption in Indonesia, various factors still influence electric vehicle purchase intentions in the region. This study uses the Theory of Planned Behavior as a theoretical foundation, adding the variables Price Value and Infrastructure Barrier. Data were collected through an online questionnaire using a non-probability sampling method.